Antimicrobial Resistance of Escherichia coli From Aquaculture Farms and Their Environment in Zhanjiang, China - Liao, Cui-Yi; Balasubramanian, Balamuralikrishnan; Peng, Jin-Ju; Tao, Song-Ruo; Liu, Wen-Chao; Ma, Yi (Frontiers in Veterinary Science, 2021)
Antimicrobial resistance (AMR) has become a major concern worldwide. To evaluate the AMR of Escherichia coli in aquaculture farms of Zhanjiang, China, a total of 90 samples from the water, soil, and sediment of three aquaculture farms (farms I, II, and III) in Zhanjiang were collected, and 90 strains of E. coli were isolated for drug resistance analysis and AMR gene detection. The results indicated that the isolated 90 strains of E. coli have high resistance rates to penicillin, amoxicillin, ampicillin, tetracycline, compound sulfamethoxazole, sulfisoxazole, chloramphenicol, florfenicol, and rifampin (≥70%). Among these antimicrobial drugs, the resistance rate to rifampicin is as high as 100%. Among the isolated 90 strains of E. coli, all of them were resistant to more than two kinds of antimicrobial drugs, the number of strains resistant to nine kinds of drugs was the largest (19 strains), and the most resistant strain showed resistance to 16 kinds of antibacterial drugs. Regarding the AMR genes, among the three aquaculture farms, the most resistance genes were detected in farm II (28 species). The detection rate of blaTEM, blaCIT, blaNDM, floR, OptrA, cmlA, aphA1, Sul2, oqxA, and qnrS in 90 isolates of E. coli was high (≥50%). The detection rate of carbapenem-resistant genes, such as blaKPC, blaIMP, and cfr, was relatively lower ( ≤ 30%), and the detection rate of mcr2 was the lowest (0). At least four AMR genes were detected for each strain, and 15 AMR genes were detected at most. Among them, the number of strains that carried 10 AMR genes was the largest (15 strains). Finally, a correlation analysis found that the AMR genes including blaTEM, blaCIT, floR, OptrA, cmlA, aac(3)-II, Sul2, ereA, ermB, oqxB, qnrA, mcr1, and mcr2 had a high correlation rate with drug resistance (≥50%). To summarize, the 90 strains of E. coli isolated from water, surrounding soil, and sediment samples showed resistance to multi-antimicrobial drugs and carried various antimicrobial resistance genes. Thus, it is essential to strengthen the rational use of antimicrobial drugs, especially the amide alcohol drugs, and control the AMR in the aquaculture industry of Zhanjiang, China.